PENERAPAN PERATURAN PERUNDANG-UNDANGAN DALAM MEMPERKUAT DEMOKRASI DI INDONESIA - Pingky Monica Hasugian; Nike Margaretha Br Sembiring, Rani Oktavia Purba, Sarah Lestari Tampubolon, Tri Bayu Armanda, Ramsul (ADISAM PUBLISHER, 2023)
Democracy is a system of government in which political decisions are made through the active participation of citizens, either directly or through their elected representatives. The basic principles of democracy include freedom of speech, human rights, elections, and government based on the will of the majority, while protecting the rights of minorities. This system provides opportunities for participation for the people in decision making. The government's efforts to realize a just and clean democracy involve transparency, the role of supervisory institutions, controlling corruption, political education, accountability, and protecting human rights. The importance of active citizen participation and monitoring of government policies also supports the achievement of better democracy. The research that Group 5 conducted was literary in nature where the researcher relied on various literature to obtain research data and used a quantitative approach because the data produced was in the form of words or descriptions. Used to identify the results of previous research findings of a related phenomenon to be studied which is a collection of facts and data in the form of theories or studies that are used as the basis for a scientific work. Qualitative research through literature study can be understood as a research method that uses descriptive data in the form of written or spoken language from people and actors who can be observed. This qualitative approach is carried out to explain and analyze individual or group phenomena, events, social dynamics, attitudes, beliefs and perceptions. Therefore, the qualitative approach research process begins with the development of basic assumptions. The results of this research show that the sustainability of democracy in Indonesia has been regulated in article 1 paragraph 2 of the 1945 Constitution which states that sovereignty is in the hands of the people and is implemented according to the constitution. and the real form of democracy in Indonesia is realized in the election of regional and state heads. which is regulated in Article 6A which regulates the direct election of the President and Vice President, Article 18 Paragraphs (3) and (4) which regulates the election of Provincial and Regency/City DPRDs, as well as the election of Governors, Regents and Mayors. The affirmation of democracy can also be seen in Article 19 Paragraph (3) of the 1945 Constitution which regulates general elections for DPR members, Article 22C Paragraph (1) general elections for DPD members.